Comparison of the inflammatory burden of truly asymptomatic carotid atheroma with atherosclerotic plaques contralateral to symptomatic carotid stenosis: an ultra small superparamagnetic iron oxide enhanced magnetic resonance study. Issue 12 (19th June 2007) - Tang, Tjun Y; Howarth, Simon P S; Miller, Sam R; Graves, Martin J; U-King-Im, Jean-Marie; Trivedi, Rikin A; Li, Zhi Yong; Walsh, Stewart R; Brown, Andrew P; Kirkpatrick, Peter J; Gaunt, Michael E; Gillard, Jonathan H
Abstract : Background: Inflammation is a recognised risk factor for the vulnerable atherosclerotic plaque. The aim of this study was to explore whether there is a difference in the degree of magnetic resonance (MR) defined inflammation using ultra small superparamagnetic iron oxide (USPIO) particles within carotid atheroma in completely asymptomatic individuals and the asymptomatic carotid stenosis contralateral to the symptomatic side. Methods: 20 symptomatic patients with contralateral disease and 20 completely asymptomatic patients underwent multi-sequence MR imaging before and 36 h after USPIO infusion. Images were manually segmented into quadrants and signal change in each quadrant was calculated following USPIO administration. Mean signal change was compared across all quadrants in the two groups. Results: The mean percentage of quadrants showing signal loss was 53% in the contralateral group compared with 31% in completely asymptomatic individuals (p = 0.025). The mean percentages showing enhancement were 44% and 65%, respectively (p = 0.024). The mean signal difference between the two groups was 8.6% (95% CI 1.6% to 15.6%; p = 0.017). Conclusions: Truly asymptomatic plaques seem to demonstrate inflammation but not to the extent of the contralateral asymptomatic stenosis to the symptomatic side. Inflammatory activity may be a significant risk factor in asymptomatic disease.